Novel metaphor and conceptual stability - Martins, Helena (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
This paper discusses three radically different approaches to the issue of novel metaphor: the classic view, according to which metaphor is itself defined by its novelty with respect to our established conceptual systems; the cognitivist view, in which novel conceptual metaphors are considered a possible but relatively rare phenomenon; and the deconstructionist view, in which novelty in metaphor is seen as either impossible or a non-issue. The possibility of reconciling valuable insights yielded in each of these approaches is explored, and the case is made for taking the matter under a non-representationalist, Wittgensteinian angle.